PENGARUH STRUKTUR AKTIVA, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PT. KAWASAN INDUSTRI MEDAN PERIODE 2014-2017 - Malau, Meilina; Syahputri, Widia; Nelsari, Yois (EDUTECH CONSULTANT, 2019)
This study aims to determine the effect of asset structure, liquidity, and firm size on the capital structure at PT. Medan Industrial Area 2014-2017 period. On the independent variables used in this study are the structure of liquidity assets, and company size while the dependent variable is the capital structure. The population used in this study is to take financial statements that exist in the structure of assets, liquidity, company size, and capital structure at PT. Medan Industrial Estate which amounts to 4 years of monthly financial statements. The sample of this study was taken using saturated sampling obtained as many as 48 samples. This study uses a quantitative research approach, a type of descriptive research, the nature of research on causal relationships. Data collection techniques with documentation techniques and data analysis using multiple linear regression analysis using simultaneous tests (F-Test) and partial tests (t-test) on the level table significant at 0.05. The results of this study show partially the structure of assets, liquidity, and company size partially have a positive and significant effect. Simultaneously the structure of assets, liquidity, and size of the company has an effect on and significant to the capital structure. The Adjusted R Square test results show 71% of the variation of the dependent variable capital structure which can be explained by the structure of assets, liquidity and size of the company while the remaining 29% is explained by other variables not explained in the study such as accounts receivable turnover, inventory turnover and total assets turnover.